Planar Microstrip Patch Antenna Arrays with Semi-elliptical Slotted Patch and ground Structure for 5G Broadband Communication Systems. Issue 1 (31st December 2022) - L. Goshu, Ayane; T. Gemeda, Mulugeta; A. Fante, Kinde
Abstract: In fifth-generation (5G) communication systems, the mm-wave (millimeter-wave) frequency band is a key aspect in overcoming the exponential increase in data traffic of the existing cellular networks, which requires compatible and low-profile antenna arrays. In this case, a microstrip patch antenna (MPA) is a viable option. However, MPA has certain limitations, such as the deterioration of the antenna's bandwidth and radiation efficiency with its substrate thickness. In addition, its gain and directivity are too low to meet the 5G systems requirements in beamforming techniques of massive MIMO systems. Thus, to ameliorate these limitations, in this paper, a microstrip patch antenna arrays (2x2, 4x4, and 8x8) with semi-elliptical shape slotted patch and etched ground structure for 5G broadband applications is proposed. The radiator element of the antenna is designed using Rogers 5880 substrate with a dielectric constant of 2.2 and thickness of 0.3449 mm. It has been designed to operate at 28 GHz in LMDS (local multipoint block distribution service) band. The performance of the proposed structure was analyzed using the CST-MW simulator. The simulation results reveal that the gain, bandwidth, and total efficiency of the studied 2x2, 4x4, and 8×8 MPA arrays are 13.24 dBi, 16.54 dBi, 21.45 dBi; 1.33 GHz, 1.461 GHz, 1.561 GHz; 97.03 %, 81.72 %, 69 %, respectively. Likewise, the return losses of these structures are −43.321 dB, −40.665 dB, and −22.678 dB, respectively. In general, all of the proposed planar semi-elliptical slotted rectangular MPA arrays offer improved performance compared to existing works and meet the requirements of 5G systems' antennas.